Genetic markers and morphometric analysis reveal past hybridization and introgression in putative Carex flava L. s.str. (Cyperaceae) hybrid populations - Blackstock, N; Ashton, P. A (Plant systematics and evolution, 2010)
The affinities of taxonomically problematic populations are typically analyzed using molecular markers. However these are less subject to selection than morphological characteristics. Consequently both approaches may be required to obtain a fuller picture of the identity and history of populations. Three putative hybrid populations within the Carex flava agg. are examined using such a dual approach with a view to elucidate their taxonomic affinities. Analysis of 11 morphometric characters using principal component analysis and examination of 17 isozyme loci revealed a more complicated history than that suggested by morphometric analysis alone. Results from this study confirm the status of an additional British population of C. flava s.str. and also strongly suggest that a population morphologically resembling Carex lepidocarpa has experienced the introgression of C. flava genes in the past. An Irish population resembling C. flava in appearance but lacking typical C. flava allozymes may be a result of local selection.